Evaluation of lettuce (Lactuca sativa L.) production under hydroponic system: Nutrient solution derived from fish waste vs. inorganic nutrient solution - Ahmed, Zienab F.R.; Alnuaimi, Alghazal K.H.; Askri, Amira; Tzortzakis, Nikos G. (My University, 2021)
Organic fresh products are appreciated and are gaining a good reputation regarding human health and environmental concerns. Despite the fact that hydroponics are commonly used in vegetable production, growers are looking for sustainable cultivation systems. Therefore, the objective of this study was to investigate the effect of using an organic-based nutrient solution (NS) derived from fish waste in a hydroponic system on the vegetative growth and production of lettuce compared to a conventional inorganic NS. Plant growth, yield, physiological and nutrient content parameters were determined. The results revealed that the overall growth and fresh biomass of the organic NS grown lettuce were relatively lower than those of the inorganic NS. Stomata density was significantly higher in inorganic grown lettuce compared to the organic one. However, the total chlorophyll, carotene, phenolic compounds, and flavonoid contents, as well as antioxidant activity were significantly higher in lettuce grown in organic NS compared to the inorganic one. Leaf nutrient content at harvest was significantly impacted by the type of used fertilizer. Based on these findings, in hydroponic system, organic liquid fertilizer derived from fish waste (as an alternative NS source) requires further improvements to achieve optimal growth and yield comparable to that of conventional inorganic NS.
Keywords: Antioxidants; Hydroponic; Lettuce; Organic nutrient; Phenols; Production